2002
DOI: 10.1088/0957-0233/13/5/316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sampling volume on the measurement of soil physical properties: simulation with x-ray tomography data

Abstract: The dependence of macroscopic soil parameters on sampling volume is currently the object of renewed research focus. In this paper, x-ray computed tomography data related to cores obtained in two different locations in a field soil are used to simulate this dependence. Several integration methods are adopted, to mimic different measuring devices. Calculation results, relative to the volumetric water content, volumetric air content, gravimetric water content and dry bulk density, demonstrate that the size (up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 34 publications
2
49
0
6
Order By: Relevance
“…resultado demonstra que podem ocorrer mudanças importantes na estrutura de amostras de solo produzidas artificialmente em razão de ciclos de U-S. Estas modificações podem se tornar extremamente relevantes é provavelmente diferente do estado anterior, ocorrido antes do primeiro ciclo de umedecimento e secamento (Baumgartl & Köck, 2004). Essa nova estrutura do solo não consegue retornar ao estado de energia original, com reflexos e mudanças no sistema poroso do solo (Bresson & Moran, 2003). Nas regiões com menor porosidade pela imagem a φ já diminui com a aplicação de apenas um ciclo de U-S (Figura 5).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…resultado demonstra que podem ocorrer mudanças importantes na estrutura de amostras de solo produzidas artificialmente em razão de ciclos de U-S. Estas modificações podem se tornar extremamente relevantes é provavelmente diferente do estado anterior, ocorrido antes do primeiro ciclo de umedecimento e secamento (Baumgartl & Köck, 2004). Essa nova estrutura do solo não consegue retornar ao estado de energia original, com reflexos e mudanças no sistema poroso do solo (Bresson & Moran, 2003). Nas regiões com menor porosidade pela imagem a φ já diminui com a aplicação de apenas um ciclo de U-S (Figura 5).…”
Section: Resultsunclassified
“…A dimensão da matriz de dados (47x40 pontos) foi escolhida com o intuito de se obter uma área representativa da amostra (Baveye et al, 2002), distante das bordas, para evitar interferência, nas imagens tomográficas, das interfaces PVC-solo-ar (Herman, 1980 ) são os coeficientes de atenuação de massa do solo e da água, respectivamente, e α é o coeficiente angular entre µ e UT, obtido a partir da calibração do tomógrafo.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Based on statistical and geostatistical analysis of data obtained in X-ray CT imagery of soils with different textures, Cı´slerova´and Votrubova ( 2002) concluded that, in the evaluation of the porosity of heterogeneous samples, the scanning direction (vertical or horizontal) seemed to have a greater influence than image resolution (determined by the size of the field of view). On data obtained by Rogasik et al (1999), Baveye et al (2002) demonstrated the dependence of soil physical characteristics (bulk density, volumetric water and air content) on the sample size, shape and positioning. For assessing the soil structural state, Rogasik et al (2003) calculated the standard deviation and the arithmetic mean of HU determined for selected regions of interest (ROIs).…”
Section: Characterization Of Soil Physical Propertiesmentioning
confidence: 96%
“…삼차 원 이미지에서 계산 가능한 토양 특성들로는 공극의 크기, 공극의 부피, 굴곡도, 길이 등이 있다 (Al-Raoush and Willson, 2005). 또한 공극의 형태학적 정보들을 바탕으로 토양 수분의 이동 특성도 예측할 수 있다 (Baveye et al, 2002;Peth et al, 2008). 이러한 공극의 정량적 특성뿐만 아닌 삼차원 이미지를 통해 공극 구조의 다양성도 계산이 가능하다.…”
Section: Introductionunclassified